the role of bhabinkamtibmas in preventing immoral acts in the territory of the Tasikmalaya district police - MUHAMMAD RICKY ANANDA NAFARIN (Advances in Police Science Research Journal, 2020)
ABSTRACTThe Role of Bhabinkamtibmas in Preventing Asusila Crime in the Tasikmalaya Regional Police StationMuhammad Ricky Ananda Nafarin, Brigtar No. AK 16.242 Since 2017 until 2019, immoral crime in the community has increased and decreased in terms of the number of cases. Had decreased in 2018 but again increased in number at the end of 2019. This should not have happened because the crime of immorality is a very crucial crime where the victim could be traumatized and also will experience a deep illness for a long period of time. Therefore, Tasikmalaya Regional Police prioritizes preemptive preventive actions to prevent immoral acts in the community. This action was carried out through a program that had been designed and arranged in such a way by the Tasikmalaya Regional Police. The approach used in this study is a qualitative approach. And data collection techniques in this study is to use observation, interviews and also use document studies. In this study also uses analysis techniques so that the data obtained is valid data. Techniques used include data reduction, data presentation and drawing conclusions.The results of the research and the conclusions that have been obtained in this study indicate that the activities of preventing the occurrence of immoral acts by Bhabinkamtibmas in the Tasikmalaya Regional police station can be concluded that they have been carried out properly and are considered sufficient. And also based on data that has been obtained and Keywords: Role of Bhabinkamtibmas, immoral crime